Penerapan Kaidah Fiqh Al-Hajatu Tanzilu Manzilata Al-Dharurah dalam Kompleksitas Perubahan Kehidupan - Fahmi , Mutiara; Sufyan, Muhammad Suhaili (Lentera: Indonesian Journal of Multidisciplinary Islamic Studies, 2024)
Al-hajatu tanzzilu manzilata al-dharurah (the need to occupy an emergency position) is a fiqh rule that is often misunderstood in its use in an effort to justify changes to a law. The reason for using this method is often based on an urgent need that seems to be the same as or at least approaching an emergency. On the basis of an emergency, a law or legal procedure can be "violated" temporarily. This study will focus on the Al-hajatu tanzzilu manzilata al-dharurah fiqh rules in order to understand the difference between the terms al-dharurah (emergency) and al-hajah (need), so that it can be ascertained which legal acts can change due to necessity and which cannot changed. After reviewing various ushul fiqh literature, it can be concluded that this rule can be developed in its application to various emergencies in life both in the fields of economics, energy, food, education, human rights, politics and worship.